Insights from metagenomics on microbial biosynthesis of vitamins B and K2 in chicken gut microbiota - Yu, Hai-Long; Hou, Xin-Wen; Zhao, Ji-Xin; Liu, Guo-Hua; Meng, Jin-Xin; Wei, Yong-Jie; Cai, Yanan; Liu, Jian; Shang, Kai-Meng; Ni, Hong-Bo; Liu, Rui; Ma, He; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe chicken gut microbiome plays a pivotal role in nutrient absorption and overall health, contributing to the biosynthesis of essential vitamins. However, the biosynthesis of vitamins B and K2 by the whole gut microbiome, as well as their abundances across different gut regions, remains largely unknown.MethodsWe employed both metagenomic sequencing and culture-based techniques, collecting a total of 25,825 genomes (25,764 metagenome-assembled genomes and 61 isolated genomes). After quality assessment and average nucleotide identity (ANI), 13,734 genomes were retained for downstream analysis.ResultsWhole-genome clustering analysis identified 2,675 species-level genome bins (SGBs), predominantly from the phyla Bacillota, Bacteroidota, Pseudomonadota, and Actinomycetota. A gene catalog comprising 9.69 million genes revealed that 195,517 genes are involved in the biosynthesis of vitamins B and K2, exhibiting significant regional variation. The large intestine exhibited greater species richness and evenness compared to the small intestine. From the 13,734 genomes, we discovered 3,063 high-quality ones capable of synthesizing at least one vitamin. Genomic analysis revealed that a mere 8.2% of genomes were capable of producing five or more vitamins, while almost half were limited to synthesizing just one. Comparative genomics of cobalamin (B12) biosynthesis highlighted the predominance of the anaerobic pathway. Additionally, changes in microbial abundance were observed, such as increased abundance of the genera Phocaeicola and Faecalibacterium during bacterial infections, and Limisoma during parasitic infections.DiscussionThis study provides detailed metagenomic insights into the capacity of chicken gut microbiome for vitamins B and K2 biosynthesis, revealing significant regional and taxonomic variations. These results suggest a collaborative microbial effort in vitamin biosynthesis, with potential implications for optimizing poultry health and nutrition through targeted microbial interventions.